SEROPOSITIVITY OF EQUINE RHINOPNEUMONITIS IN KAZAKHSTAN - Abeuov , Kh.B.; Burashev , Y.D.; Rystaeva , R.A.; Omarova , Z.D.; Tulendibaev , A.B.; Aubakir , N.A.; Ermekbai , T.T.; Argimbayeva , T.U.; Alibekova , D.A.; Abduraimov , Y.O.; Rsalyev , A.S. (Eurasian Journal of Applied Biotechnology, 2025)
The study aimed to conduct monitoring research to determine the seroprevalence of equine rhinopneumonitis in Kazakhstan. PCR analysis of the samples showed negative results; however, serological analysis revealed the presence of antibodies to equine herpesvirus (EHV) in several regions. Based on the results of the serological analysis, antibodies to EHV serotype 1 were detected in the Akmola, Abay, East Kazakhstan, Jambyl, Almaty, and Jetisu regions. The seroprevalence of this virus ranged from 66.6% to 100% in the Akmola, Abay, East Kazakhstan, and Almaty regions, while in the Jetisu and Jambyl regions, it was 50% or less. The results of the ELISA test showed the presence of antibodies to EHV serotype 4 in almost all regions, except for the Ulytau, Kostanay, and Pavlodar regions. Compared to EHV-1, the seroprevalence of EHV-4 was higher in almost all regions of Kazakhstan. The seroprevalence in the Akmola, Abay, East Kazakhstan, Almaty, Jetisu, West Kazakhstan, Aktobe, Kyzylorda, Jambyl, and Karaganda regions was 100%. Meanwhile, in the Atyrau, North Kazakhstan, Mangystau, Ulytau, and Kostanay regions, antibodies were almost undetectable.